An Analysis of Digital Competencies of Accountants in the Digital Age: A Case Study of Nakhon Pathom Province - สุขจำลอง พรทิพย์; กาละปุก นวกรณ์; จงอิทธิ กานต์รวี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were to 1) study the digital competency levels of accountants operating in Nakhon Pathom Province. The sample consisted of 333 registered accountants practicing in Nakhon Pathom. The research instrument used for data collection was a questionnaire. Data were analyzed using mean and standard deviation. The research findings revealed that the overall digital competency of the accountants was at a high level (x̄= 4.04, S.D. = .72). When considering all four dimensions it was found that Digital Adaptation to Change had the highest mean at a high level (x̄= 4.06, S.D. = .67), This was followed by Digital Technology Knowledge (x̄= 4.01, S.D. = .72) and Digital Problem Solving Skills (x̄= 4.00, S.D. = .76)and the lowest mean score was found in the use of digital technology (x̄= 4.10, S.D. = .71).